2006
DOI: 10.1002/rcm.2397
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐assisted laser desorption/ionization imaging mass spectrometry for direct measurement of clozapine in rat brain tissue

Abstract: Matrix-assisted laser desorption/ionization hyphenated with quadrupole time-of-flight (QTOF) mass spectrometry (MS) has been used to directly determine the distribution of pharmaceuticals in rat brain tissue slices which might unravel their disposition for new drug development. Clozapine, an antipsychotic drug, and norclozapine were used as model compounds to investigate fundamental parameters such as matrix and solvent effects and irradiance dependence on MALDI intensity but also to address the issues with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 40 publications
9
125
0
Order By: Relevance
“…As demonstrated with the previous cobimetinib experiments, tissue that was washed with ammonium citrate and presprayed with cyclohexane prior to matrix application yielded optimal extraction with a~8-fold gain in overall average signal intensity ( Table 2). As a result, a more ubiquitous distribution of clozapine was observed ( Figure 5e) and is in line with previously reported autoradiography data, which detected clozapine distributed throughout the brain [20]. Ammonium formate, a more commonly used wash buffer [7,8], was also tested to determine if it can yield the same signal gains as ammonium citrate.…”
Section: Resultssupporting
confidence: 89%
“…As demonstrated with the previous cobimetinib experiments, tissue that was washed with ammonium citrate and presprayed with cyclohexane prior to matrix application yielded optimal extraction with a~8-fold gain in overall average signal intensity ( Table 2). As a result, a more ubiquitous distribution of clozapine was observed ( Figure 5e) and is in line with previously reported autoradiography data, which detected clozapine distributed throughout the brain [20]. Ammonium formate, a more commonly used wash buffer [7,8], was also tested to determine if it can yield the same signal gains as ammonium citrate.…”
Section: Resultssupporting
confidence: 89%
“…For small molecules analysis, two main classes may be distinguished -exogenous drugs and endogenous metabolites. Exogenous drugs have been studied in MALDI-MSI far later than proteins (since 2004) for different targets such as olanzapine (antipsychotic) [85][86][87], imatinib [87], vinblastine [88], and banoxantrone [89] (cancer drugs). Among endogenous metabolites, lipids such as glycerophospholipids and glycosphingolipids or simple lipids like cholesterol, diacylglycerols, or triacylglycerols have been extensively investigated [90].…”
Section: Maldi Mass Spectrometry Imagingmentioning
confidence: 99%
“…Soltwisch et al employed a combination of four peptides within their recent study [7], but no analysis of the effect of fluence on these molecules individually or of this increased complexity on the observed trends was explicitly presented. A 2006 study by the Korfmacher group showed the detected ion response to laser energy for clozapine and norclozapine in dosed rat brain tissue, but no measurement of the size of the irradiated area was carried out, nor was this performed in a spatially resolved (imaging) mode, meaning the spatial distribution of the drug within the tissue cannot be discounted as a significant contributor to the trends seen [10]. Lagarrigue et al discussed the spectral differences resulting from different size irradiated areas and fluence regimes in a tissue imaging context but no energy measurements were presented to accompany these data [11].…”
Section: Introductionmentioning
confidence: 99%